Dentistry under general anesthesia in the patient with epilepsy. Case report and literature review - López Torres, Ana Cristina (2020)
The clinical care of patients with epilepsy (EP) associated with intellectual disability (ID) represents a challenge for the stomatologist because of its diﬃcult behavioral management. These patients will require alternatives to carry out a successful dental treatment. General anesthesia (AG), is an alternative to the failure of behavioral management techniques, existence of systemic commitment that warrants it, specialized medical access distant from the place of residence or due to particular circumstances of each case. We present the case of a 27-year- old male patient, with a diagnosis of EP associated with ID, of diﬃcult behavioral management treated under general anesthesia in the Special Patients Stomatology service of the Peruvian University Cayetano Heredia. Objective: This article seeks to present a review of the literature and Comprehensive Dental Treatment under general anesthesia of a patient with Epilepsy associated with moderate Intellectual Disability. Conclusions: Patients with these underlying pathologies are prone to present deterioration of the oral organ, so they will require constant stomatological beneﬁts. Due to the low collaboration of this type of patients, the AG should be considered as an alternative to provide the TOI in a single operative act.